SASI SEBAGAI BUDAYA KONSERVASI SUMBER DAYA ALAM DI KEPULAUAN MALUKU - Nadia Putri Rachma Persada; Fachruddin M Mangunjaya; Imran SL Tobing (Jurnal Ilmu dan Budaya, 2018)
Sasi is an effort to conserve natural resources on land and sea by the indigenous people of Maluku. The practices are based on the knowledge of the community, sasi set the time or period when a resource can be harvested in order not to disrupt its life cycle. Sasi can be regarded as one of the local wisdom that can assist conservation efforts categorized by IUCN in criterion VI. There are two types of sasi which is managed by customs and sasi which is managed by religious institutution such as mosque and a church, where religious and adat leaders usually interrelated and cooperate. Sasi protects marine biota that has high economic value or the target market consumption and local communities. Sasi protect three common marine biota are lompa (Thryssa baelama), sea cucumber (Holothuroidea spp) and lola (Trochus niloticus). Sasi implement customary law and all the rules applied have good sanctions in the form of fines or sanctions that are supernatural or mystical. As an effort to conserve marine and fishery resources, sasi has a role from various aspects in terms of ecology, social culture and economy. Along with the development and modernization, sasi tradition challenges by some contstrains such as social and political dynamics.